1989
DOI: 10.1128/jb.171.4.1967-1973.1989
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial RNA polymerase genes rpoC1 and rpoC2 correspond to rpoC of Escherichia coli

Abstract: The DNA-dependent RNA polymerase (ribonucleoside triphosphate:RNA nucleotidyltransferase, EC 2.7.7.6) of cyanobacteria contains a unique core component, -y, which is absent from the RNA polymerases of other eubacteria (G. J. Schneider, N. E. Tumer, C. Richaud, G. Borbely, and R. Haselkorn, J. Biol. Chem. 262:14633-14639, 1987). We present the complete nucleotide sequence of rpoCl, the gene encoding the -y subunit, from the heterocystous cyanobacterium Nostoc commune UTEX 584. The derived amino acid sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…The genes are colinear with the rpoB and rpoC genes of E. coli, but homology to the P' subunit of E. coli is divided between two genes, rpoCI and rpoC2. The same split in the rpoC gene is present in the cyanobacterium N. commune UTEX 584 (47) and in plant chloroplasts (19,20,38). While the organization of the cyanobacterial and chloroplast rpoBCIC2 genes resembles the rpoBC operon of E. coli, the Anabaena and chloroplast genes do not lie distal to any ribosomal protein genes (3a, 19, 20).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The genes are colinear with the rpoB and rpoC genes of E. coli, but homology to the P' subunit of E. coli is divided between two genes, rpoCI and rpoC2. The same split in the rpoC gene is present in the cyanobacterium N. commune UTEX 584 (47) and in plant chloroplasts (19,20,38). While the organization of the cyanobacterial and chloroplast rpoBCIC2 genes resembles the rpoBC operon of E. coli, the Anabaena and chloroplast genes do not lie distal to any ribosomal protein genes (3a, 19, 20).…”
Section: Resultsmentioning
confidence: 93%
“…A region of DNA homologous to part of the E. coli gene encoding 3' (rpoC) has been isolated from another cyanobacterium, Nostoc commune UTEX 584 (47). Se-quencing of this region showed that homology to E. coli rpoC is split between two linked genes, rpoCl and rpoC2, in the Nostoc DNA (47).…”
mentioning
confidence: 99%
“…4, top). 40,41) The core enzyme functions in mRNA polymerization, but requires the sigma () subunit for specific transcription initiation at the promoter. 36,42) General switching in transcription is mainly due to the modulated promoter selectivity of multiple RNAP holoenzymes combined with the replacement of a common core enzyme with several different sigma factors, responding to environmental or internal cellular change.…”
Section: A Light-induced Sigma Factor and Positive Regulationmentioning
confidence: 99%
“…Preliminary sequencing showed that the two genes are adjacent on the chromosome in the order rpoB rpoC (9), as in other eubacteria that have been investigated (1,17,28) (in the cyanobacteria, rpoC is split into two genes i.e., rpoC1 and rpoC2 [48]). Chater (13) isolated three classes of rifampin-resistant mutants of S. coelicolor, designated rifA, rifB, and rifC.…”
mentioning
confidence: 99%